The Role of Cardiac MRI in the Management of Ventricular Arrhythmias in Ischaemic and Non-ischaemic Dilated Cardiomyopathy. Issue 3 (2019) - Nelson, Tom; Garg, Pankaj; Clayton, Richard H; Lee, Justin
No abstract available